Hippocampal contributions to semantic memory retrieval: strategy-specific impairments in transient global amnesia - Sandikci, Vesile; Ebert, Anne; Marzina, Annika; Platten, Michael; Szabo, Kristina; Hoyer, Carolin (The journal of neuropsychology, 2025)
Transient global amnesia (TGA), a transient memory disorder in clinical neurology, is a unique clinical model for the study of hippocampal dysfunction and its implications for memory processes. While data are rather unequivocal concerning the relevance of the hippocampus for episodic memory, there is considerable dispute about its role for semantic memory. This study aimed at exploring how hippocampal impairment, which underlies the clinical presentation of TGA, affects semantic memory retrieval, particularly with regard to different retrieval strategies. Data from the acute and post-acute phase of 17 TGA patients and 17 healthy controls matched on socio-demographic factors were collected. Categorical word fluency tasks were differentiated into three retrieval strategies: first, with activation of episodic-spatial memory content; second, with novel and flexible linking of semantic memory content and third, with activation of overlearned semantic memory content. We find that hippocampal impairment during TGA significantly restricts semantic word fluency performance, with the degree of impairment depending on the retrieval strategy used and most pronounced when flexible relinking of semantic content is required. Our results suggest an important hippocampal contribution to semantic retrieval, especially in connection with novel and flexible linking of semantic content. They may furthermore be practically relevant for the early differential diagnosis and therapy of memory disorders.